Penerapan Teknik Steganografi Teks pada Format File PDF - Silaen, Calvin; Frans Panjaitan; Marihot Tambunan (JURNAL QUANCOM: QUANTUM COMPUTER JURNAL, 2025)
This research aims to implement steganography by embedding text messages into PDF files using metadata methods and securing the messages through AES encryption. The project consists of several stages, beginning with the selection of a PDF file to serve as the medium for embedding. Users can then input the message they wish to embed. This message will subsequently be encrypted using the AES method, which is designed to protect the content from unauthorized access. Following this, the encrypted message will be embedded into the PDF file via metadata, ensuring that the structure and appearance of the PDF remain unchanged. During the extraction phase, users possessing the appropriate key can retrieve the embedded message and decrypt it to read its content. The implementation results demonstrate that this method successfully maintains the confidentiality of the message without compromising the structure or appearance of the PDF file, ensuring that the message is accessible only to those with the correct decryption key, thereby enhancing the security of sensitive information storage and transmission.